INFOMAR data supports offshore energy development and marine spatial planning in the Irish offshore via the EMODnet Geology portal. Issue 1 (February 2021) - Guinan, J.; McKeon, C.; O'Keeffe, E.; Monteys, X.; Sacchetti, F.; Coughlan, M.; Aonghusa, C. Nic
No abstract available